2009
DOI: 10.1111/j.1365-2753.2008.01055.x
|View full text |Cite
|
Sign up to set email alerts
|

Potentially inappropriate urinary catheter indwelling among long‐term care facilities residents

Abstract: The prevalence of long-term UC indwelling among Taiwanese LTCF residents was high and a high proportion of their UC may be removable. A national audit and introducing a practice guideline for continence care in LTCFs may help to promote quality of care for institutionalized older people in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Previous studies revealed that the prevalence of indwelling urinary catheters or nasogastric tube insertion among long-term care facility residents in Taiwan is higher than that in the United States and European countries [26-29]. Long-term placement of urinary catheters or enteral feeding through nasogastric tubes can cause patient discomfort and lead to complications such as tube dislodgement, mucosal injury, infection and pressure ulcers, resulting in a decreased quality of life [26,30]. The rate of tube replacement of home healthcare patients in Taiwan deserves more attention.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that the prevalence of indwelling urinary catheters or nasogastric tube insertion among long-term care facility residents in Taiwan is higher than that in the United States and European countries [26-29]. Long-term placement of urinary catheters or enteral feeding through nasogastric tubes can cause patient discomfort and lead to complications such as tube dislodgement, mucosal injury, infection and pressure ulcers, resulting in a decreased quality of life [26,30]. The rate of tube replacement of home healthcare patients in Taiwan deserves more attention.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, many urinary catheters among residents in long-term care facilities in Taiwan were potentially removable. 13 In Europe, the prevalence of long-term urinary catheter use in elderly home care recipients ranged from 0 to 23% in 11 different countries.…”
Section: Discussionmentioning
confidence: 99%
“…13 However, many urinary catheters among residents in long-term care facilities in Taiwan were potentially removable. 13 In Europe, the prevalence of long-term urinary catheter use in elderly home care recipients ranged from 0 to 23% in 11 different countries. 16 In this study, the prevalence of long-term urinary catheter use is significantly higher than European countries, and is higher than the previous report from Taiwan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the most important method of prevention of CAUTI is to use an IUC only when necessary (appropriate) and to remove them when no longer indicated (Meddings et al, 2014). Inappropriate urethral catheterisation use is well documented in the literature in both acute (Chang, 2014; Gokula et al, 2004; Jansen et al, 2012; Tiware et al, 2012) and long-term care settings (Chen et al, 2009; Dingwall and McLafferty, 2006; Lomas et al, 2009; McNulty et al, 2006). Gokula et al (2004) report inappropriate use in 54% of catheterised patients, and of those catheterised only 13% had an explicit documented reason.…”
Section: Introductionmentioning
confidence: 99%